Islamic business ethics in small and medium enterprises (SMEs) : an analysis - Mohd Zulkifli Muhammad; Mohd Fadil Mohd Yusof; Hanudin Amin (2012)
Islamic business ethics is essential for SME industry. The challenge of Islamic business ethics is to make that inevitable ethical decision making explicit to make it better and in line with the Shariah principles. Far from being anti-business, ethics actually provides essential support for maximizing long-term business value. In an Islamic system, ethics and business are not only compatible but also inseparable because Islam is not just a religion. It projects a perfect way of life. A human manner and behavior in small and medium enterprises cannot be effectively clarified without references to the Islamic ethics which can manage it. Thus, this paper will discuss the issues pertaining to the concept of business ethics in Islamic perspective toward Small and Medium Enterprises (SMEs). This is because of their significant contribution in the Malaysian economics at large. Furthermore, this study also explains how SME could adapt the Islamic business ethics system in their day-to-day business activities.